The challenges of the transnational litigation in the European Union: has the notion of matters relating to a contract been extended too much in Brussels i Regultation? - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The goal of this paper is to analyze the ECJ judgment of 14 July 2016 in the Granarolo case. This issue highlights again interpretative aspects in relation to the Brussels I Regulation that will affect the Brussels I bis Regulation. These are what to must be understood by contractual matter or by a contract of sale or of provision of services. But the reality is that this interpretation goes beyond the purely technical and legal aspects. These issues that arise in the ruling imply challenges that the parties in a transnational litigation in the European Union must take into account when organizing the procedural strategy to be followed.
Keywords: matters relating to a contract; non-contractual liability; contract of sale of goods; contract of provision of services